Reforming National Law in the Context of Digital Transformation - Verbovaya, Olga; Ashyraliyeva, Bayan; Kaliyeva, Gulmira; Salimbayeva, Zhana; Sagalbayeva, Roza (Law, State and Telecommunications Review, 2024)
[Purpose] The purpose of this article is to identify the main challenges and prospects of national legislation in Kazakhstan and to determine the development vectors for selected branches of law in the context of digitalisation. [Methodology/Approach/Design] The study employed the following methods: analysis and synthesis, statistical analysis, rating method, and comparison. The study identified key innovations in Kazakhstan’s legal framework for digitalisation. The main objectives in the implementation of the Digital Kazakhstan state programme and the key target indicators defined within this programme have been studied, and the results of the implementation of this programme have been assessed. [Findings] The dynamics of e-government and e-participation indices for the Republic of Kazakhstan are examined. [Practical Implications] The findings of the study can be used by public authorities and policymakers to improve the efficiency of further decision-making regarding the transformation of national law in the context of digital transformation. [Originality/Value] The findings of this study have provided an outline of the main challenges and prospects for national law in the context of digitalisation, revealing the trends for the further development of individual branches of law.